Effective Router Assisted Congestion Control for SDN - Sofia Naning Hertiana; Adit Kurniawan; Hendrawan Hendrawan; Udjianna Sekteria Pasaribu (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Router Assisted Congestion Control (RACC) was designed to improve endto- end congestion control performance by using prior knowledge on network condition. However, the traditional Internet does not provide such information, which makes this approach is not feasible to deliver. Our paper addresses this network information deficiency issue by proposing a new congestion control method that works on the Software Defined Network (SDN) framework. We call this proposed method as PACEC (Path Associativity Centralized Congestion Control). In SDN, global view of the network information contains the network topology including link properties (i.e., type, capacity, power consumption, etc.). PACEC uses this information to determine the feedback signal, in order for the source to start sending data at a high rate and to quickly reach fair-share rate. The simulation shows that the efficiency and fairness of PACEC are better than Transmission Control Protocol (TCP) and Rate Control Protocol (RCP).